Liver function, tolerability and satisfaction during treatment with ulipristal acetate in women with fibroids: a single center experience. (3rd May 2020) - Del Forno, Simona; Degli Esposti, Eugenia; Salucci, Paolo; Leonardi, Deborah; Iodice, Raffaella; Arena, Alessandro; Raimondo, Diego; Paradisi, Roberto; Seracchioli, Renato
Abstract: The aim of the study was to evaluate liver function in women treated with ulipristal acetate (UPA) and to assess the tolerability and satisfaction during treatment. This Cross-sectional study included women with symptomatic uterine fibroids subjected to one or more 3-month treatment courses of 5 mg UPA daily. Following European Medical Agency's prescriptions, women were asked about symptoms potentially related to liver damage and had blood tests done, to assess serum levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Data on side effects, tolerability and satisfaction with the therapy were obtained during a phone interview. A total of 162 women completed the study with a mean treatment duration of 1.8 ± 0.9 cycles. No increased AST and ALT serum levels were detected and no woman reported symptoms suggestive of liver injury. The majority of women reported improvement of fibroids-related symptoms and a high degree of satisfaction with treatment. More than half of women had side effects, in most cases not as severe as to discontinue therapy. Ulipristal acetate did not worsen liver function or cause severe organ injury and showed high tolerability and satisfaction profiles. Therefore, we believe that it can still be considered a valuable option in the treatment of uterine fibroids.